Self- and proxy-reported outcomes after surgery in people with disorders/differences of sex development (DSD) in Europe (dsd-LIFE). Issue 3 (June 2021) - Rapp, Marion; Duranteau, Lise; van de Grift, Tim C.; Schober, Justine; Hirschberg, Angelica L.; Krege, Susanne; Nordenstrom, Anna; Roehle, Robert; Thyen, Ute; Bouvattier, Claire; Kreukels, Baudewijntje P.C.; Nordenskjold, Agneta; et al.
Summary: Background: Surgery is performed in many individuals with disorders/differences of sex development (DSD). Irreversibility of some surgical procedures, lack of information about the procedures, and lack of follow-up care for physical and psychological outcomes, lead to wish for more knowledge from both surgeons and patients. After the consensus conference in 2006, multidisciplinary care is provided to a higher degree with psychological support and more restricted surgical procedures. Outcome studies after genital surgery often lack of patient's perspective. Objective: To describe surgical procedures in relation to diagnosis, to evaluate the outcomes of surgery through genital examination, and through patient's and observer's satisfaction with the anatomical and functional result after genital surgery. Study design: In a cross-sectional clinical study performed in six European countries in 2014/15, we have included 500 participants where surgery was performed, from a total of 1040 adolescents (≥16years) and adults with a DSD. Diagnoses included Turner syndrome (n = 301), mixed gonadal dysgenesis (45, XO/46, XY; n = 45), Klinefelter syndrome (n = 218), XYY (n = 1), 46, XY DSD (n = 222) and 46, XX DSD (n = 253). Study protocol included clinical report files, an optional gynecological or urological examination, patient reported outcomes including received surgical interventions, satisfaction with appearance and function after surgery, and impact of the surgical procedure on life. Results: Five hundred participants had received genital or breast surgery, with the highest rate in 46, XY DSD and the lowest in Turner syndrome. Altogether; 240 participants had feminizing surgery, 112 had masculinizing surgery, and 217 underwent gonadectomy. Physicians evaluated anatomical appearance at genital examination as poor in less than 10%. Dissatisfaction with anatomical appearance was reported by 22% of the participants, dissatisfaction with function by 20%. Being (very) dissatisfied with anatomical appearance and function was reported by 13% of the study participants. Most participants reported no impact, or positive impact, of the surgical procedures on their lives, but 29% experienced a negative effect of gonadectomy on their life. Discussion: There might be a selection bias and/or a recall bias for participating in our studies. Due to poor data quality about surgical procedures performed in the past, we also relied on participants memory about surgical procedures in their past. Ideally, patient reported outcomes should be evaluated both before and after surgical procedures. Conclusion: A vast majority are satisfied with appearance and function, but still genital or breast surgery have a long-lasting effect on patient's life. Self-reported satisfaction is usually lower than the observer's evaluation regarding both appearance and function. Summary Figure Satisfaction with anatomy and function after genital surgery in individuals with DSD (appearance: n = 244; function: n = 257) (n = total number of participants). Summary Figure